Cutaneous Amelanotic Signet-Ring Melanoma in a Siberian Tiger (Panthera tigris altaica). (November 2021) - Hensel, Martha E.; Wiener, Dominique J.; Edwards, John F.
Summary: A 15-year-old male white Siberian tiger ( Panthera tigris altaica ) was evaluated for an elevated, ulcerated, cutaneous mass on the right flank. The mass was removed by excisional biopsy and submitted for histopathology. Based on distinct histological features of intracytoplasmic globular material and positive immunohistochemical staining for Melan-A and vimentin, an amelanotic signet-ring melanoma was diagnosed. While in domestic cats this neoplasm is associated with malignancy and a short survival time, the tiger had no local recurrence or related clinical disease approximately 4 years post surgery. Cutaneous melanocytic tumours are rare in big cats, and the findings in this case suggest that amelanotic signet-ring melanoma is not as malignant as its counterpart in domestic cats. Graphical abstract: Cutaneous amelanotic signet-ring melanoma in a Siberian tiger. Neoplastic cells have abundant eosinophilic globular, inclusion-like cytoplasm (signet-ring appearence), eccentric round to oval nuclei with finely stippled chromatin and prominet central round 'owl's eye' nucleoli. (Bars, 50 μm, respectively). Image 1